Implementation of Center Learning Model for Early Childhood in Kemala Bhayangkari 05 Kindergarten, Banten Region - Alfia Batshila; Asya Alifa; Felicia Yorenda; Dian Surya Aprilyanti; Sipa Unnaziah; Luthfiyah Robbiyati Shofa; Sumiati; Nanda Shafira Ashadi; Siti Dewi Winengsih; Hanifa Almira Nanda (Contemporary Journal of Applied Sciences, 2025)
Early childhood, according to Yuliani Sujiono (2014), is a child aged from birth to 6 years. This period is very crucial in the formation of character, personality, and intellectual abilities of children. Early childhood education can be understood as a learning process that focuses on developing potential including cognitive, emotional, social, physical-motor, language, and moral aspects. The center learning model is an educational approach specifically aimed at early childhood, with an emphasis on development through play activities. This approach combines two main elements, namely circle time and play centers. This research method uses a qualitative descriptive approach. Data collection is carried out through observation, interviews, documentation, and field notes. Learning at Kemala Bhayangkari 05 Kindergarten, Banten Region, shows significant effectiveness in implementing the center learning model.